Agentivité ou autonomie ? Pour une théorie critique de la vulnérabilité - Marie Garrau (Genre, Sexualité et Société)
Academic studies on vulnerability have first focused on the absence of “vulnerability” in contemporary political theory. Then, they focused on its conceptual design and normative implications. More recent studies concentrate on the relations between vulnerability and agency and urge us to question the common identification of vulnerability with passivity. The idea that we should overcome the opposition between vulnerability and agency is very important but may lead to a number of problems. More specifically, it can deprive the category of vulnerability of the critical role it had come to play in philosophy and the social sciences. How then should we conceive the relations between vulnerability and agency? In this text, I try to answer this question by defending two arguments: I first argue that, for both theoretical and political reasons, we should neither oppose nor identify vulnerability and agency. If we are to build a critical conception of vulnerability, we must figure out an alternative to these undesirable options. Second, I argue that such an alternative can be found in tying together the concepts of vulnerability and agency with a third concept, namely relational autonomy.